2020
DOI: 10.5230/jgc.2020.20.e38
|View full text |Cite
|
Sign up to set email alerts
|

Successful Management of a Tracheo-gastric Conduit Fistula after a Three-field Esophagectomy with Combined Sternocleidomastoid Muscle Rotation Flap and Histoacryl Injection Treatment

Abstract: Tracheo-gastric conduit fistula is an extremely rare but severe complication that is difficult to manage. Conservative care, esophageal or tracheal stent placement, or cutaneomuscular flaps have been suggested; however, no definite treatment has been proven. We report a case of tracheo-gastric conduit fistula that occurred after a minimally invasive radical three-field esophagectomy. Following the primary surgery, the diagnosis was made while evaluating the patient's frequent aspiration and coughing. Conservat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Clinically, NGT is routinely inserted at the bedside, which does not allow accurate insertion of the NGT into the gastric antrum area, 22 and the tube may enter the airway through the fistula, increasing patient discomfort and the risk of fistula damage. If the gastric tube is placed above the gastric antrum, the gas from the airway enters the gastric cavity via the fistula, and the negative pressure drum of the NGT often sucks out the gas, which prevents the gastric juices and contents from being sucked out effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, NGT is routinely inserted at the bedside, which does not allow accurate insertion of the NGT into the gastric antrum area, 22 and the tube may enter the airway through the fistula, increasing patient discomfort and the risk of fistula damage. If the gastric tube is placed above the gastric antrum, the gas from the airway enters the gastric cavity via the fistula, and the negative pressure drum of the NGT often sucks out the gas, which prevents the gastric juices and contents from being sucked out effectively.…”
Section: Discussionmentioning
confidence: 99%
“…(Figure 5) A small case series reported the use of histoacryl based skin glues to successfully plug the fistula. 35 If the patient does not respond to conservative approaches, surgical intervention could be attempted. Nardella et al 34 demonstrated successful closure of both fistulous connections through a right thoracotomy.…”
Section: Gastric Conduit Refluxmentioning
confidence: 99%
“…Literature on this entity is mainly limited to case reports. [34][35][36] The primary cause of tracheobronchial fistulas after esophagectomy is anastomotic leak leading to peri-conduit inflammation and erosion into the airway. 34,35 Partial thickness damage and/or ischemia to the membranous portion of trachea or main stem bronchi during esophagectomy may also play a role.…”
Section: Gastric Conduit Refluxmentioning
confidence: 99%
See 1 more Smart Citation